For the sequence defined by a_"1"=2, a_"n+1"=1/(3-a_"n")a1=2,an+1=13an, how to show that it is bounded below by 0?

For the sequence defined by a_"1"=2, a_"n+1"=1/(3-a_"n")a1=2,an+1=13an?

(a) Assuming that sequence is decreasing, show that it is bounded below by 0

(b) Explain why this means it must have a limit.

(c) Find the limit lim_(nrarroo)a_"n"

2 Answers
Mar 21, 2018

a) Let's start by writing the first few terms of the sequence.

a_1 = 2
a_2 = 1/(3 - 2) = 1
a_3 = 1/(3 - 1) = 1/2
a_4 = 1/(3 - 1/2) = 2/5
a_5 = 1/(3 - 2/5) = 5/13

As you can see, each term is getting smaller, but there is no way it's going to go below 0 because for this to happen, we would need a_n > 3, and since a_(n + 1) < a_n, and a_1= 2, a_n will never be greater than 3 therefore we can say that the sequence is bounded below by 0.

b) Because this sequence converges to 0 as x approaches to infinity, we can say lim_(n-> oo) a_n = 0. This means that the sequence is maybe not divergent, but that the limit test is inconclusive (we would need another test to check for convergence).

c) Here's the formal proof that lim_(n -> oo) a_n = 0:

lim_(n -> oo) a_n =(1/a_n)/(3/a_n - a_n/a_n) = 0/(-1) = 0

As found above.

Hopefully this helps!

Mar 21, 2018

See below.

Explanation:

Taking

a_(k+1) = 1/(3-a_k)
a_k = 1/(3-a_(k-1))

we have

a_(k+1)-a_k = (a_k-a_(k-1))/((3-a_k)(3-a_(k-1)) and

abs(a_(k+1)-a_k) = abs(a_k-a_(k-1))/abs((3-a_k)(3-a_(k-1))

and for 0 le a_k < 2 we have

abs(a_(k+1)-a_k) < abs(a_k-a_(k-1))

then the sequence converges for

0 le a_k < 2

The convergence limit can be attained when

a_oo = 1/(3-a_oo) or

3a_oo -a_oo^2-1=0 giving

a_oo = 1/2(3pm sqrt5) with the feasible

a_oo = 1/2(3-sqrt5)